Social Media in the College Classroom - Richardson, Marianna E. (International Dialogues on Education Journal, 2015)
The power of social media in our global society has been labeled as a social revolution that is changing the way we live, work, communicate, and learn. College students are surrounded by and engrossed in social media. University professors are realizing the necessity of incorporating social media in their classrooms. Social media has become a major component of distance learning and massive open on-line courses (MOOCs) increasing the availability of a college education to students who could not previously afford it or who geographically had no access to it. The rising use of social media in college classrooms is changing the delivery of information and the formation of educational communities. In addition, it is advancing the democratization of universities and the opportunities for international students to experience a world-class education.